IN VITRO DIGESTIBILITY OF RICE STRAW-BASED RATIONS OF DAIRY COWS CONTAINING FERMENTED CONCENTRATE BY Saccharomyces cerevisiae AND Effective Microorganisms-4 (EM-4) - Iman Hernaman; Ana Rochana Tarmidi; Tidi Dhalika (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
Concentrate was used to improve rice straw-based rations of dairy cows. Rejected foods can be used to formulate concentrate but it can contain unwanted materials. This research aimed to know the best of fermentation time and rations formulation. Research phase 1 was to observe nutrient and energy contents of concentrate fermented by Saccharomyces cerevisiae and EM-4 at 0, 3, and 6 days. Phase 2 was to evaluate the use of the best fermented concentrate of the phase 1 to be used in the ration on in vitro rumen degradability using treatments as follows: 1) 50% rice straws + 50% concentrate, 2) 50% rice straws + 25 concentrate + 25% fermented concentrate, 3) 50% rice straws + 50% fermented concentrate. This study used completely randomized design and the collected data were analyzed by Contrast Orthogonal test. The results showed that crude protein (CP) increased but crude fiber (CF) and bruto energy decreased due to concentrate fermentation. A 3 day fermentation resulted in the highest (P<0.05) CP (14.48%) and the lowest CF (17.01%). The use of fermented concentrate at 50% in the ration resulted in the highest (P<0.05) digestibility of dry matter (63.68%) and organic matter (58.70%). It can be concluded that concentrate fermentation at 3 days by Saccharomyces cerevisiae and Effective Microorganisms-4 (EM-4) was the best treatments. Its use in rice straws-based rations of dairy cows at 50% and result in the highest digestibility of dry matter and organic matter.